Al-Fārābī’s Thought of Ideal State - Mahmuda Mahmuda (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2019)
The research data was collected by documenting qualitative data from various literature related to the concept of the establishment of the State Ideal / Main (al-Madīnah al-Fāḍilah). This study takes the idea or the idea of a character famous Muslim philosopher who is considered as a reference in the conduct of a concept study. The obtained and analyzed by using a historical approach to find an appropriate concept for establishing a State Ideal / Main. From the results of this study, a description of the establishment of a country must have an idea of thought in creating an Ideal State. This research can not be separated from scholarly Muslims as al-Fārābī, which may explain how a country is considered excellent and good enough for the people who feel it. The concept of forming the state of the ideal is described as the role of religion, morality, and society in the formation of a highly sustainable state to achieve a state of desire in the establishment of the ideal.